Anisotropic plastic deformation of single crystals of the MAX phase compound Ti3SiC2 investigated by micropillar compression. (December 2018) - Higashi, Masaya; Momono, Shogo; Kishida, Kyosuke; Okamoto, Norihiko L.; Inui, Haruyuki
Abstract: The anisotropic deformation behavior of single crystals of Ti3 SiC2 has been investigated at room temperature as a function of loading axis orientation and specimen size by micropillar compression tests. Basal slip is found to be only the operative slip system at room temperature. The a /3[1 2 ¯ 10] basal dislocation responsible for basal slip dissociates into two partial dislocations of the Shockley-type and glides between Ti1 and Si atomic layers, as confirmed both experimentally and theoretically. The CRSS value for basal slip increases with the decrease in the specimen size, following an inverse power-law relationship with a very large power-law exponent of about 1.0, which is almost the upper limit of those reported for FCC metals. When the loading axis is parallel to the basal plane, kink band formation occurs only after the occurrence of basal-plane delamination and the subsequent activation of a -dislocations gliding on the basal plane. Kink bands consists of a /3[1 2 ¯ 10] basal edge dislocations of the same sign, each of which had glided between Ti1 and Si atomic layers. These results indicates that the kink formation can simply be interpreted by the classical dislocation-based kink-formation model. Graphical abstract: Image 1